Konsep Dasar Ilmu Pengetahuan Sosial (IPS) dan Ilmu, Teknologi, dan Masyarakat (ITM): Tujuan, Keterkaitan, dan Dampaknya Terhadap Perkembangan IPTEK - Qoidul Khoir (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article aims to review and understand the basic concepts of Social Studies (IPS), the purpose of social studies education, as well as the basic concepts of Science, Technology, and Society (ITM), and their interrelationships. This article shows that: first, the concept of ITM emphasizes more on the development of students' personality; second, in the context of Science, Technology, and Society, there are positive and negative impacts that affect the development of science and technology (IPTEK).